Exercise capacity is not decreased in children who have undergone lung resection early in life for congenital thoracic malformations compared to healthy age‐matched children. Issue 10 (24th July 2017) - Dunn, Ashlee; Pearce, Kasey; Callister, Robin; Collison, Adam; Morten, Matthew; Mandaliya, Payal; Platt, Lauren; Dascombe, Ben; Kumar, Rajendra; Selvadurai, Hiran; Robinson, Paul D.; Mattes, Joerg
Abstract: Purpose: The purpose of this study was to compare (i) the exercise capacity and (ii) lung function prior to and immediately post cardiopulmonary exercise tests (CPET) of children who underwent early life lung resection for Congenital Pulmonary Airway Malformations (CPAM) to healthy control children. Method: Eight children with CPAM (four males, age 9.6 ± 1.8 years) and eight control children without respiratory disease (three males, age 9.4 ± 1.4 years) performed a CPET on a cycle ergometer, during which maximal oxygen consumption (V̇O2max ) and heart rate were measured. Prior to and immediately post CPET, lung function measures including Nitrogen Multiple Breath Washout (MBW) and spirometry were performed. Results: There were no significant between group differences in pre CPET lung function ( P >  0.05) or maximal exercise capacity (V̇O2max CPAM: 39.4 mL . kg −1. min −1, Control: 40.5 mL . kg −1. min −1 ). Post CPET, FEV1 was significantly lower in the CPAM group, with two participants diagnosed subsequently with exercise induced bronchospasm based on post‐CPET spirometry and follow‐up clinical investigations. Conclusion: Early life lung resection for CPAM does not appear to have negative implications for exercise capacity later in childhood. Clinicians should be aware that dyspnoea following exercise may be due to asthma rather than residual effects of CPAM in these children.